1964
DOI: 10.1021/ja01075a013
|View full text |Cite
|
Sign up to set email alerts
|

Electron Paramagnetic Resonance Studies of the Electronic Structures of Bis(maleonitriledithiolato)copper(II), -nickel(III), -cobalt(II), and -rhodium(II) Complexes

Abstract: Vol. 86 Fig. 10.-Rotatory dispersion curve of the L-histidine-copper complex resolved into a simple Cotton effect and a Cotton effect similar to those of the cobalt, nickel, and zinc complexes.the many-electron model to this chromophoric electron. Looking at complex I (imidazole plane), it would be reasonable to take the most polarizable 2-direction in the direction of charge transfer. The y-direction would be in the imidazole plane and the x-direction would be perpendicular to that plane. All of the groups li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
146
1
1

Year Published

1967
1967
2005
2005

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 325 publications
(168 citation statements)
references
References 1 publication
20
146
1
1
Order By: Relevance
“…Using the above coordinate system the ground state of (dX2-Y2)2(dXZ)2(dZ2)2(dyz) has been reported for four cobalt complexes (10,12,13,21 has been attributed to most other complexes (1 1, 14, 16, 17, 22-24). In the case of one type of CON,complex,Engelhardt et al (23) have proposed a (d,,)2(dy,)2(d,2)2(dx2~y2) ground state while Urbach et al (1 5) have proposed the more usual (dX2-y2)2(dXZ)2(dyZ)2(dZ2) ground state.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Using the above coordinate system the ground state of (dX2-Y2)2(dXZ)2(dZ2)2(dyz) has been reported for four cobalt complexes (10,12,13,21 has been attributed to most other complexes (1 1, 14, 16, 17, 22-24). In the case of one type of CON,complex,Engelhardt et al (23) have proposed a (d,,)2(dy,)2(d,2)2(dx2~y2) ground state while Urbach et al (1 5) have proposed the more usual (dX2-y2)2(dXZ)2(dyZ)2(dZ2) ground state.…”
Section: Introductionmentioning
confidence: 94%
“…No regular pattern is observed in the hyperfine A values. In the few single crystal studies done (9)(10)(11)(12)(13), the large g value is always'found to be in the plane deCan. J. Chem.…”
Section: Introductionmentioning
confidence: 99%
“…Five single crystal studies of low spin Co(I1) complexes are known to the authors (1,(12)(13)(14)(15) and only two (1, 15) are of complexes having oxygen and nitrogen bonding to the cobalt ion. Zelewsky and Fierz (1) in their study of N, N1-ethylenebis(salicylideneiminato)cobalt(II), [Co(salen)], claimed that only a ' B, ground state would explain their results but they provided no details.…”
Section: Solutions and Powders In Which It Is Not Possiblementioning
confidence: 99%
“…The axis normal to the molecular plane or z axis is taken to be that axis with the large g value and A value in the copper system and is found to be in the 23 plane of the crystal. The x axis has been assigned by an analogy with similar Co(I1) complexes (1, 13,14) in which the large g value is always associated with the x axis. The growth habits of this crystal also support this assignment, since growth of the crystal along the long axis or y axis of molecule would be poor, which is the case for the 1 axis of the crystal.…”
Section: M(amben)mentioning
confidence: 99%
“…result in an electronic T I too short to allow observation of esr spectra even a t 77 K. The magnetic susceptibility measured in the solution and 63 the paramagnetic shifts observed in the nmr spectrum of the complex are strong indications [5] A, = K + P that there is indeed a paramagnetic species here 4 57 which is not a pure S = 112 state. The magnetic is defined likewise.…”
Section: Discussionmentioning
confidence: 88%